2015
DOI: 10.1007/s13197-015-1726-2
|View full text |Cite
|
Sign up to set email alerts
|

Third generation snacks manufactured from orange by-products: physicochemical and nutritional characterization

Abstract: A mixture of orange vesicle flour, commercial nixtamalized corn flour and potato starch was extruded using a Brabender Laboratory single screw extruder (2:1 L/D). The resulting pellets were expanded by microwaves. Expansion index, bulk density, penetration force, carotenoid content, and dietary fiber were measured for this third-generation snack and optimum production conditions were estimated. Response surface methodology was applied using a central composite rotatable experimental design to evaluate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 17 publications
10
27
0
Order By: Relevance
“…Figure shows a small difference in BD between 2G and 3G products, but directly expanded products had lower values. Similar to this study, the previous study showed increase of BD with higher moisture content (Tovar‐Jiménez et al, ). One‐way ANOVA showed that the type of product had a significant influence on BD ( p < .05), unlike the content and type of cake (Table ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure shows a small difference in BD between 2G and 3G products, but directly expanded products had lower values. Similar to this study, the previous study showed increase of BD with higher moisture content (Tovar‐Jiménez et al, ). One‐way ANOVA showed that the type of product had a significant influence on BD ( p < .05), unlike the content and type of cake (Table ).…”
Section: Resultssupporting
confidence: 91%
“…It can be seen that BD increases with the addition of defatted cakes for all samples, which has already been established in previous investigations (Bisharat et al, ; Stojceska, Ainsworth, Plunkett, & Ibanoglu, ; Tovar‐Jiménez et al, ). Different types of by‐products increase the BD of products, which is in correlation with the ER, lower expansion, higher BD, since thinner cell walls are formed in the products with higher EI (Bisharat et al, ; Stojceska et al, ; Tovar‐Jiménez et al, ). However, it can also depend on the type and content of fibers and/or extrusion conditions.…”
Section: Resultssupporting
confidence: 85%
“…Extrusion is a continuous, high-capacity, energy-efficient cooking process at high temperatures and short times, which transforms food materials into a plastic-like paste that forms shaped products with a special texture after expansion (Singh et al 2012;Tovar-Jiménez et al 2015;Singh et al 2016). In addition, extrusion causes the destruction of heat-labile compounds like trypsin inhibitors, hemagglutinins, gossypol, lipoxigenases, peroxidases and lipoxidases (Yu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Physical technological aspects like heat transfer, mass transfer, and residence time distribution have a strong impact on the food and feed properties during extrusioncooking and can drastically influence the final product quality. Currently, extrusion-cooking as a method is used for the manufacture of many food and feed products as well as for modification a variety of other materials like thermoplastic starch or cellulose [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Pellets are the extrusion-cooked semiproducts for snacks production. They can be kept in dry storage for 12 months due to theirs compact structure and low humidity [1,2,17].…”
Section: Introductionmentioning
confidence: 99%